Paroxetine treatment in an animal model of depression improves sperm quality. - Reyhane Aghajani; Marziyeh Tavalaee; Niloofar Sadeghi; Mazdak Razi; Parviz Gharagozloo; Maryam Arbabian; Joël R Drevet; Mohammad Hossein Nasr-Esfahani (PLoS ONE)
Depression in mammals is known to be associated with poor reproductive capacity. In males, it has been associated with decreased efficiency of spermatogenesis as well as the production of spermatozoa of reduced structural and functional integrity. Although antidepressants are effective in correcting depressive states, there is controversy regarding their effectiveness in restoring male reproductive function. Here, using an animal model of depression induced by a forced swim test, we confirmed that depression is accompanied by impaired male reproductive function. We further show that administration of a conventional antidepressant of the serotonin reuptake inhibitor class (paroxetine) impairs male reproductive performance in terms of sperm production and quality when administered to healthy animals. Intriguingly, when paroxetine is administered to "depressed" animals, it resulted in a complete restoration of the animal's ability to produce sperm that appears to be as capable of meeting the parameters evaluated here as those of control animals. The one-carbon cycle (1CC) is one of the most important metabolic cycles that include the methionine and folate cycles and plays a major role in DNA synthesis, amino acids, and also the production of antioxidants. Our results show that depression affects the main components of this cycle and paroxetine on healthy mice increases homocysteine levels, decreases glycine and vitamin B12, while in depressed mice, it increases folate levels and decreases vitamin B12. Thus, paroxetine exerts negative impacts on male reproductive function when administered to healthy animals and it well correlate with the altered sperm parameters and functions of depressed animals, and its mechanism remains to be explored.